Grinding of silicon wafers: a review from historical perspectives - Pei, Zhijian J.; Fisher, Graham R.; Liu, J. (My University, 2008)
The majority of semiconductor devices are built on silicon wafers. Manufacturing of high quality silicon wafers involves several machining processes including grinding. This review paper discusses historical perspectives on grinding of silicon wafers, impacts of wafer size progression on applications of grinding in silicon wafer manufacturing, and interrelationships between grinding and two other silicon machining processes (slicing and polishing). It is intended to help readers to gain a more comprehensive view on grinding of silicon wafers, and to be instrumental for research and development in grinding of wafers made from other materials (such as gallium arsenide, germanium, lithium niobate, sapphire, and silicon carbide).
Keywords: Abrasive; Gallium arsenide; Germanium; Grinding; Lapping; Lithium niobate; Machining; Polishing; Sapphire; Semiconductor material; Silicon; Silicon carbide; Silicon wafer